Effect of feeding mid- or zero-tannin faba bean cultivars differing in vicine and covicine content on diet nutrient digestibility and growth performance of weaned pigs. Issue 2 (18th April 2022) - Nyende, Protus W; Wang, Li Fang; Zijlstra, Ruurd T; Beltranena, Eduardo
Abstract: To prioritize what cultivars to grow to feed pigs, five faba bean cultivars including three zero-tannin, high vicine and covicine cultivars (Snowbird, Snowdrop, Tabasco), and two medium-tannin, lower vicine and covicine cultivars (Fabelle and Malik) were fed to compare effects on diet nutrient digestibility and growth performance of weaned pigs. A total of 260 pigs (8 ± 1.2 kg), weaned at 20 ± 1 d of age housed 2 barrows and 2 gilts/pen were fed 1 of 5 dietary regimens starting 1-week post-weaning for 4 weeks in a randomized complete block design. Diets including each cultivar at 20% or 30% provided 10.2 and 10.1 MJ net energy (NE )/kg and 1.3 and 1.2 g standardized ileal digestible (SID ) lysine (Lys )/MJ NE in phases 1 and 2, respectively. Digestibility data were analyzed using PROC GLIMMIX and growth performance data were analyzed using PROC MIXED with pen as experimental unit. Fabelle contained the most condensed tannins (CT ; 0.53%) but the least vicine (0.04%) and covicine (0.01%). Zero-tannin cultivars contained little CT (<0.2%) but had the greatest vicine (0.5%) and covicine content (0.4%). For phase 1, diet apparent total tract digestibility (ATTD ) of dry mater (DM ), gross energy (GE ), crude protein (CP ), digestible energy (DE ), and NE values did not differ among cultivars. For phase 2, diet ATTD of DM and GE were greatest ( P < 0.05) for Snowdrop and Tabasco, intermediate for Fabelle, and lowest for Malik; Snowbird was not different from Fabelle or Malik. Diet ATTD of CP was greatest ( P < 0.05) for Tabasco, intermediate for Snowbird, and lowest for Malik; Snowdrop was not different from Tabasco or Snowbird, and Fabelle was not different from Snowbird or Malik. Diet DE and NE values were greatest ( P < 0.05) for Tabasco, intermediate for Fabelle and Snowdrop, and lowest for Snowbird; Malik was not different from Fabelle or Snowbird. For the entire trial (d 0–28), daily feed disappearance and weight gain for pigs fed Fabelle were 10% greater ( P < 0.05) than those fed Malik; pigs fed zero-tannin cultivar diets were intermediate. Pigs fed Fabelle were 1.6 kg heavier ( P < 0.05) than those fed Malik at the end of the trial; pigs fed zero-tannin cultivar diets were intermediate. In conclusion, growth performance of pigs fed faba bean cultivar diets was more related to feed disappearance than diet nutrient digestibility. Vicine and covicine instead of condensed tannin content of faba bean cultivars seemed more relevant to growth performance in weaned pigs.